2010
DOI: 10.3109/09553001003734501
|View full text |Cite
|
Sign up to set email alerts
|

Indication of cocarcinogenic potential of chronic UMTS-modulated radiofrequency exposure in an ethylnitrosourea mouse model

Abstract: This pilot study indicates a cocarcinogenic effect of lifelong UMTS exposure (4.8 W/m(2)) in female B6C3F1 descendants subjected to pretreatment with ethylnitrosourea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 40 publications
1
40
1
Order By: Relevance
“…Effects on tumour susceptibility in mice exposed to a UMTS (universal mobile telecommunications system) test signal from fetal time for up to 24 months were studied by Tillmann et al [45]. Animals were exposed to UMTS fields with intensities of 0, 4.8, and 48 W/m 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects on tumour susceptibility in mice exposed to a UMTS (universal mobile telecommunications system) test signal from fetal time for up to 24 months were studied by Tillmann et al [45]. Animals were exposed to UMTS fields with intensities of 0, 4.8, and 48 W/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The results by Tillmann et al [45] gained further interest based on the results in a follow-up study published in 2015 [46]. The exposure levels were 0 (sham), 0.04, 0.4, and 2 W/kg SAR.…”
Section: Resultsmentioning
confidence: 99%
“…The group that was ENU-treated and UMTS-exposed at 4.8 W/m 2 exhibited an increased rate of lung tumours and an increased incidence of lung carcinomas as compared with the controls treated with ENU alone. The authors concluded that the study demonstrated a co-carcinogenic effect of lifelong UMTS exposure in female mice subjected to pretreatment with ENU (18). …”
Section: Introductionmentioning
confidence: 96%
“…The effects on tumour susceptibility in mice exposed to a UMTS test signal from the fetal period for up to 24 months was studied by Tillman et al (18). Animals were exposed to UMTS fields with intensities of 0, 4.8 and 48 W/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…As there is evidence that mobile phones cause a thermal, heating effect [30], it could be argued that inner ear temperature fluctuations between the conditions may have confounded the findings. On the other hand, it has also been reported that any changes in cerebral blood flow due to mobile phone radiation, assessed by positron emission tomography, are unlikely to be temperature-related [31,32]. This issue needs further investigation.…”
Section: Discussionmentioning
confidence: 93%